Tinjauan Sirkulasi Ruang Pada Fasilitas Penyandang Tunanetra - Setiawan, Trianita Anugerah; Maharlika, Febry (Fakultas Desain Universitas Komputer Indonesia, 2021)
People with visual impairments are people with disabilities who have visual impairments. People with visual impairments are divided into two, namely low vision and totally blind. In doing activities, the blind use aids or assisted by someone who is accompanying them. They can carry out activities in public facilities, therefore every public facility needs to meet the standards of comfort for persons with disabilities including blind people. To make it easier for the visually impaired to meet their needs, contour processing and circulation space are needed for them. Circulation of space consisting of horizontal and vertical circulation in public facilities for the visually impaired will be different from the sighted person. Usually blind people will use a stick as a mobility aid, so that wider circulation is needed than the sighted person. One of the public facilities in Bandung is the Social Rehabilitation Center for Persons with Sensory Disabilities